Characteristics of Managerial Effectiveness -A Study of Bank Managers in Punjab - Kansai, Rajeev (Gyan Management Journal, 2007)
Th pre ·ent paper intend to evaluate the characteristic of managerial effectivene ·s in commercial banks in Patiala and Sangrur district of Punjab. The study reveals that managers should have the knowledge how the loans are utilized, the need for checking goals periodically, formulation of banking policies cooperatively, daily balancing of books, maintaining line and staff relationship and winning the cooperation and goodwill of local people etc. functioning of its banking industry. Our country is not an exception. Bank in India meet the short-term and medium term financial needs and thus help the economy to operate smoothly. The financial needs become even more ignificant in view of the requirements of agricultural sector and the sma11 . cale industries, which con titute the backbone of our economy by contributing about 50 percent of the total national income. Banks therefore, must operate in such a way so that they improve the effectiveness of producing goods and service in the nation. Effectiveness banks operation is, therefore. indispensable.